Christian Approaches to Philosophy and Education in Gregory of Nazianzus - Terezēs, Chrēstos Ath. ca. 20./21. Jh. (Augustinianum, 2024)
In this article we approach the question of philosophy and its relation to education in the Christian light of Gregory of Nazianzus. In particular, based on the example of Heron chosen by the Cappadocian Father, we follow the presentation and discussion of the principles, both on theoretical and practical level, which should govern the thought and life of the man who is active in the capacity of a Christian and a philosopher within society. These principles gradually constitute a genuine proposal for a philosophical way of being and education, in the context of which Christianity can make eclectic use of Ancient Greek thought. The predominant thing that is formed is a concrete Christian Ethics directly intertwined with Christian Metaphysics, which is considered to be able to define Anthropology in all its aspects.